Demand-Supply Balancing in Manufacturing Operations - Coker, Joakim (My University, 2010)
The recent financial turbulence has shown that while all industrial manufacturing companies’ demand is exposed to fluctuations, the nature of their business still requires these companies to make long-term commitments to their plants and personnel. So for this reason the ability to balance demand and supply through improved operations management is truly a competitive advantage, which will help a company survive poor times and gain ground from its competition when markets revive. The contemporary supply chain management-related theories introduced are divided into the six categories of Supply Chain Structure, Supply Chain Flexibility, Demand Management, Capacity Management, Inventory Management and Pricing, Revenue and Yield Management. As pre-existing outlines for the study were not found, numerous international and domestic articles, books and other publications were researched to define the central issues. In the empirical part of the study the theories were presented to the Chief Operations Officers of several Finnish industrial manufacturing companies, and they were asked about the relevance and application of these topics in their businesses. The key findings show that while only few companies currently carry out these practices systematically, most of them possess much interest and great potential for improving their operations through these methods.
Keywords: Supply Chain Management; Operations Research; Strategy; Industrial Manufacturing; Finland; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|